Performance evaluation and stability analysis of malt barley (Hordeum vulgare L.) varieties for yield and quality traits in Eastern Amhara, Ethiopia - Abebe Assefa; Getawey Girmay; Tesfaye Alemayehu; Alemu Lakew (CABI Agriculture and Bioscience)
Abstract Background Barley (Hordeum vulgare L.) is an annual cereal crop that belongs to the grass family Poaceae of the tribe Triticeae. It is the fifth most important cereal crop after teff, wheat, maize and sorghum in area coverage in Ethiopia. Important malting barley characteristics include kernel size, kernel protein content, extractable malt and diastatic power. Malt barely is an important crop in the study area; however, the productivity is low in the area varying from 15 kg ha−1 to 21 kg ha−1. The aim of the study was to identify high yielding, standard quality and stable malting barley variety to the study areas and similar agro-ecologies. Field experiments were conducted using eight improved malt barely varieties during the main cropping seasons (from the first week of July to end of October) in 2016 and 2017 at two selected sites Dehana (Amede work) and Lalibela (Medagai)) in north east Ethiopia. Data on grain yield and yield related traits, and quality attributes were recorded. Days to 50% heading (DH), and days to 90% maturity (DM) were recorded on plots basis. Plant height (PH, in cm), spike length (SPL, in cm), and number of seeds per spike (SPS) were measured on five randomly selected plants per plot of the central four rows. Mean grain yield (GY; grams of grain produced per plot, converted in kg ha−1), above ground dry biomass or biological yield (BY; dry weight of the above ground harvested biomass grams per plot, in kg ha−1) and thousand grain weight (TGW; weight of 1000 kernels, in grams) were measured on whole plots. Data were analyzed using SAS software program and significance of the mean difference was tested in least significant difference Test (LSD). Result The analysis of variance for grain yield and quality traits showed that the main effects of both genotypes and environments, and their interaction effect, were highly significant (P ≤ 0.01). The environment main effect accounted for 42%, 38% and 50% of the total grain yield, thousand kernel weight and kernel protein content variation, respectively. The average grain yield across varieties varied from 1652 kg ha−1 to 3377 kg ha−1. Conclusions Three malting barley varieties (IBON174/03, EH1847 and Bahati) were found to be relatively high yielding, stable for grain yield and full fill the quality parameters. Therefore, these varieties are recommended for production. A further study is required on agronomic practices and brewing quality attributes in malt barley.